177Lu-DOTATATE peptide receptor radionuclide therapy in metastatic or advanced and inoperable primary neuroendocrine tumors of rare sites - Pradeep Thapa; Rahul Parghane; Sandip Basu (World Journal of Nuclear Medicine)
The present study aimed at exploring the patient and imaging characteristics of primary neuroendocrine tumors (NETs) of rare sites who presented with metastatic and/or advanced inoperable stages and therefore was considered for peptide receptor radionuclide therapy (PRRT) with 177Lu-DOTATATE. A retrospective analysis was undertaken of these patients focusing on the aforementioned aspects. All patients underwent dual-tracer molecular functional imaging with somatostatin receptor (SSTR)-based imaging (with either 99mTc-HYNIC-TOC or 68Ga-DOTATATE) and 18fluorine fludeoxyglucose positron emission tomography-computed tomography as the pretherapy assessment. Based on the qualitative uptake of tracer in SSTR imaging, the lesions were divided into four categories Grade 0–III. The response was assessed post-PRRT by three parameters: (i) symptomatic response, (ii) biochemical response (serum tumor marker), and (iii) objective imaging response. The response profiles under each of these scales were assessed utilizing predefined criteria (detailed in methods). The overall response classification into partial response, stable disease, and progressive disease was done based on documentation of similar scale/category of at least two parameters among the triple parametric assessment. A total of nine patients (7 males, 2 females; age range: 33–59 years) with rare site primary NET were found: The primary sites included ureter (n = 1), sacrococcygeal (n = 1), esophagus (n = 1), thymus (n = 3), and mediastinum (n = 3). Treatment response assessment was undertaken in eight patients who received more than 2 cycles of PRRT with 177Lu-DOTATATE. In this response assessment group (n = 8), the patients received 2–5 cycles and follow-up duration ranged from 5 to 48 months. Symptomatic responses and better quality of life were observed in 4/8 (50%) patients, stable symptomatic disease in 3/8 (37.5%), and progression in 1/8 patients (12.5%). Biochemically, partial response was seen in 3/8 (37.5%), stable values was seen in 3/8 (37.5%), and progression of tumor marker was seen in 2/8 (25%) patients. Morphologically, partial response was seen in 2/8 (25%), stable disease in 5/8 (62.5%), and progressive disease in 1/8 (12.5%) patients. On overall assessment, 2/8 patients (25%) demonstrated partial response, 4/8 stable disease (50%), and 2/8 progressive disease (25%) at the time of assessment. As per the RECIST 1.1, seven patients had stable disease and one patient had progressive disease. No specific correlation could be obtained between dual-tracer molecular imaging features and the response likely due to small population of the study group. Overall, there was evidence of excellent disease stabilization, and symptom palliation with 177Lu-DOTATATE PRRT was documented in these advanced or metastatic NETs of various rare sites.